2022
DOI: 10.1155/2022/1527488
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Susceptibility Patterns of ESβL Producers Isolated from the Mobile Phones

Abstract: Mobile phones have become an indispensable part of human lives for communication, education, and entertainment activities. This study aims to evaluate the diversity pattern of bacterial contaminants on mobiles and to check antibiotic resistance profiles in 105 samples. The study revealed a contamination of 51% in men and 49% in women, the highest in the 21- to 30-year age group, evidencing the extreme use of mobiles by teenagers. The study observed Gram-negative bacteria (63%) versus Gram-positive bacteria (37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It impairs a number of bacterial processes, including DNA replication along with protein synthesis; they ultimately result in bacterial or cell death. The main interactional mechanism is this [ 17 , 18 ]. Additionally, oxidative stress that affords another pathway for cellular disruption can be commenced from the production of reacting oxygen substance on the surface of AgNPs [ 19 , 20 ].…”
Section: Resources and Procedures For Experimentsmentioning
confidence: 99%
“…It impairs a number of bacterial processes, including DNA replication along with protein synthesis; they ultimately result in bacterial or cell death. The main interactional mechanism is this [ 17 , 18 ]. Additionally, oxidative stress that affords another pathway for cellular disruption can be commenced from the production of reacting oxygen substance on the surface of AgNPs [ 19 , 20 ].…”
Section: Resources and Procedures For Experimentsmentioning
confidence: 99%
“…1 Among the various CoNS species, the most prevalent organisms include Staphylococcus epidermidis, followed by Staphylococcus citrus, Staphylococcus saprophyticus, Staphylococcus pseudintermedius, Staphylococcus capitis, Staphylococcus hominis, and Enterococcus faecalis. 2 Sepsis is a medical condition that can be life-threatening. It occurs when the body's response to an infection causes inflammation all over the body, and Staphylococcus capitis (S. capitis) is one of the types of bacteria that has been linked to sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%